Answer:
9x + 6
Step-by-step explanation:
<u>Step 1: Distribute</u>
5x + (x + 6) + 3x
5x + x + 6 + 3x
<u>Step 2: Combine like terms</u>
5x + x + 6 + 3x
9x + 6
Answer: 9x + 6
Answer:
You happen to know what I am looking at? Theres no photos :(
Step-by-step explanation:
Answer:
false. slope is calculated by rise over run
Answer:
line m i think
Step-by-step explanation:
Answer:
a) ![4.5 \times 10^{11}](https://tex.z-dn.net/?f=4.5%20%5Ctimes%2010%5E%7B11%7D)
b) ![3.5 \times 10^{3}](https://tex.z-dn.net/?f=3.5%20%5Ctimes%2010%5E%7B3%7D)
Step-by-step explanation:
a) We have to simplify the below expression in standard form.
The expression is ![(5\times 10^{3}) \times (9 \times 10^{7})](https://tex.z-dn.net/?f=%285%5Ctimes%2010%5E%7B3%7D%29%20%5Ctimes%20%289%20%5Ctimes%2010%5E%7B7%7D%29)
Now, ![(5\times 10^{3}) \times (9 \times 10^{7})](https://tex.z-dn.net/?f=%285%5Ctimes%2010%5E%7B3%7D%29%20%5Ctimes%20%289%20%5Ctimes%2010%5E%7B7%7D%29)
= ![(9 \times 5) \times (10^{3} \times 10^{7})](https://tex.z-dn.net/?f=%289%20%5Ctimes%205%29%20%5Ctimes%20%2810%5E%7B3%7D%20%5Ctimes%2010%5E%7B7%7D%29)
=
{Since
}
= ![45 \times 10^{10}](https://tex.z-dn.net/?f=45%20%5Ctimes%2010%5E%7B10%7D)
=
(Answer)
b) We have to simplify the below expression in standard form.
The expression is ![(7\times 10^{5}) \div (2 \times 10^{2})](https://tex.z-dn.net/?f=%287%5Ctimes%2010%5E%7B5%7D%29%20%5Cdiv%20%282%20%5Ctimes%2010%5E%7B2%7D%29)
Now, ![(7\times 10^{5}) \div (2 \times 10^{2})](https://tex.z-dn.net/?f=%287%5Ctimes%2010%5E%7B5%7D%29%20%5Cdiv%20%282%20%5Ctimes%2010%5E%7B2%7D%29)
= ![(7 \div 2) \times (10^{5} \div 10^{2})](https://tex.z-dn.net/?f=%287%20%5Cdiv%202%29%20%5Ctimes%20%2810%5E%7B5%7D%20%5Cdiv%2010%5E%7B2%7D%29)
=
{Since
}
=
(Answer)